APPLICATION AND EFFECTIVENESS OF STEM EDUCATIONAL METHODOLOGY IN PRESCHOOL ORGANIZATIONS (International journal of artificial intelligence, 2025)
This article analyzes the application of STEM (Science, Technology, Engineering, Mathematics – Science, Technology, Engineering and mathematics) educational methodology in preschool educational organizations and its effectiveness. It is noted that through the STEM approach, children from an early age develop cognitive development, creativity, logical thinking, problem solving, and professional-oriented initial visions are formed. This methodology deepens children's perception of the environment through scientific observation, creating a solid foundation for them to master the sciences well in the future. Because STEM education is based on practical aspects, the child associates the knowledge they are learning with real life, which develops his ability to think independently and take an innovative approach.